A note on the facticity of animal trials in early modern Britain; or, the curious prosecution of farmer Carter’s dog for murder - Beirne, Piers (Crime, law and social change, 2011)
For a century or so there has been a lively debate on the meaning of animal trials in early modern and medieval Europe. One unresolved issue in this debate is the geographical and jurisdictional incidence of animal trials, including their facticity in Britain. This essay explores some neglected evidence in this regard, namely, three British animal trials identified in E.P. Evans’ (1906/1987) authoritative text The Criminal Prosecution and Capital Punishment of Animals.